Devising a method to form reference images to provide high-precision navigation for unmanned aerial vehicles when changing geometric viewing conditions - Sotnikov, Alexander; Sydorenko, Ruslan; Mykus, Serhii; Zakirov, Serhii; Vlasov, Ihor; Shkvarskyi, Oleksandr; Samsonov, Yuriy; Petik, Andrii; Nechaus, Andrii; Rikunov, Oleh (Eastern-European Journal of Enterprise Technologies, 2025)
The object of this study is the process of forming a minimally sufficient set of reference images for use in correlation-extreme navigation systems when changing the navigation parameters of unmanned aerial vehicles. The paper reports the results related to solving the task to form a set of reference images taking into account changes in the navigation parameters of high-speed unmanned aerial vehicles and their impact on the information features of images. The effect of changing the viewing angles and altitude on the formation of segmented images by energy characteristics has been studied. The discrete steps for navigation parameters were established, at which the correlation between image fragments is maintained at the level of 0.9. These values are from 90 to 120 meters in height and from 15° to 25° in angular parameters. The effect of the structure of segmented images on the selection of the reference object has been studied. It is shown that the feature of the selection of the reference object in the segmented image is the value of the fractal dimension 2.998…2.999. The study was conducted in the MATLAB software environment using the source image selected from Google Earth Pro. The application of the selected sequence of constructing fragments of reference images has made it possible to identify objects that have the best characteristics in terms of signal-to-noise ratio and structure with increasing discreteness of navigation parameters. The method differs from known ones in using the image structure as information features along with the brightness and contrast of objects. This would reduce the number of fragments of reference images while maintaining the accuracy indicator. The results could be implemented in secondary processing systems of correlation-extreme navigation systems used on high-speed unmanned aerial vehicles